Predictive parameters of early postoperative complications in Crohn’s disease: Single team experience - Atasoy, Deniz; Aghayeva, Afag; Bilgin, İsmail Ahmet; Erzin, Yusuf; Erenler Bayraktar, İlknur; Baca, Bilgi; Karahasanoğlu, Tayfun; Hamzaoğlu, İsmail (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: Most of the patients with Crohn’s disease (CD) may require at least one surgical procedure over their lifetime. However, these patients tend to have a high incidence of postoperative complications. The aim of this retrospective study was to investigate the predictive parameters of postoperative complications in CD. Materials and Methods: All consecutive patients with CD between March 2001 and March 2016 who underwent bowel resection were included to this study. Postoperative complications were divided as; major complications including anastomotic leakage, ostomy complications, acute mechanical intestinal obstruction and hemorrhage, and minor complications including wound infection. Results: A total of 147 patients (74 females, 73 males) with a mean age of 36±11.9 years met the inclusion criteria. Behaviors of CD were stricturing in 90 (62%), fistulizing in 45 (30%) and inflammatory in 12 (8%) patients. Minimally invasive approach was applied in 35% (n=51) of the patients. Twentysix (17%) patients had early (≤30 days) postoperative surgical complications including anastomotic leak (n=10), intra-abdominal bleeding (n=2), complications related to ostomy (n=2), acute mechanical intestinal obstruction (n=1) and wound infection (n=11). Only fistulizing disease behavior was associated with early postoperative complications (p=0.014). Conclusion: This study suggests that postoperative complications are still more common in fistulizing CD. Surgical approach did not affect the complication rate. The decision should be individualized according to the prominent risk factors and surgeons’ preference. Cite this article as: Atasoy D, Aghayeva A, Bilgin İA, et al. Predictive parameters of early postoperative complications in Crohn’s disease: Single center experience. Turk J Gastroenterol 2018; 29: 406-10.